ANALISIS DAMPAK KELUARGA BROKEN HOME TERHADAP MINAT BELAJAR SISWA DI SMP NEGERI 1 KARANGDOWO - Malvino Lingga Fajaro; Dwi Nastiti; Ghozali Rusyid Affandi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This research is motivated by the procrastination behavior carried out by students. Many students do not complete school assignments, many students do not attend school and prefer to joke around while learning. The purpose of this study is to determine the differences in academic procrastination in terms of the level of emotional regulation in students of Hangtuah 5 Middle School, Sidoarjo. The study used a comparative quantitative method. The population in this study amounted to 174 students. The sampling technique in this study used a saturated sampling technique. Data collection used a psychological scale with a Likert scale model, namely the academic procrastination scale and the Emotional Regulation scale. Data analysis used the independent sample T-Test analysis technique with the help of the SPSS 26.0 for Windows program. The results of the study showed that there were differences in academic procrastination in terms of emotional regulation owned by students of Hangtuah 5 Middle School, Sidoarjo with a sig. (2-tailed) value of 0.000 (<0.05) and a t value = -2.215.